Glycogen Synthase Kinase 3β Inhibition Prevents Monocyte Migration across Brain Endothelial Cells via Rac1-GTPase Suppression and Down-Regulation of Active Integrin Conformation - Rom, Slava (American Society for Investigative Pathology, 2012)
Glycogen synthase kinase (GSK) 3β has been identified as a regulator of immune responses. We demonstrated previously that GSK3β inhibition in human brain microvascular endothelial cells (BMVECs) reduced monocyte adhesion/migration across BMVEC monolayers. Herein, we tested the idea that GSK3β inhibition in monocytes can diminish their ability to engage the brain endothelium and migrate across the blood-brain barrier. Pretreatment of primary monocytes with GSK3β inhibitors resulted in a decrease in adhesion (60%) and migration (85%), with similar results in U937 monocytic cells. Monocyte-BMVEC interactions resulted in diminished barrier integrity that was reversed by GSK3β suppression in monocytic cells. Because integrins mediate monocyte rolling/adhesion, we detected the active conformational form of very late antigen 4 after stimulation with a peptide mimicking monocyte engagement by vascular cell adhesion molecule-1. Peptide stimulation resulted in a 14- to 20-fold up-regulation of the active form of integrin in monocytes that was suppressed by GSK3β inhibitors (40% to 60%). Because small GTPases, such as Rac1, control leukocyte movement, we measured active Rac1 after monocyte activation with relevant stimuli. Stimulation enhanced the level of active Rac1 that was diminished by GSK3β inhibitors. Monocytes treated with GSK3β inhibitors showed increased levels of inhibitory sites of the actin-binding protein, cofilin, and vasodilator-stimulated phosphoprotein-regulating conformational changes of integrins. These results indicate that GSK3β inhibition in monocytes affects active integrin expression, cytoskeleton rearrangement, and adhesion via suppression of Rac1-diminishing inflammatory leukocyte responses.